Fecal microbiota composition and function are associated with anxiety and depression in patients with inflammatory bowel disease - Zhan Wang; Minsi Zhou; Yan Dang; Xueping Huang; Chenyue Xu; Fang Xu; Xinyi Xu; Peng Li; Shutian Zhang; Haiyun Shi; Jing Wu (PLoS ONE, 2025)
Background and aims Increasing prevalence of anxiety and depression are found in patients with inflammatory bowel disease (IBD). Altered gut microbiome may affect the brain, resulting in psychiatric symptoms. We aimed to analyze the feature of gut microbiota in IBD patients with anxiety or depression. Methods Anxiety and depression symptoms were assessed by the Hospital Anxiety and Depression Scale (HADS). Stool samples were collected from IBD patients, and the 16S rRNA sequencing was used to detect fecal microbiota. Metabolites were detected by Liquid Chromatography-Mass Spectrometry (LC-MS). Results Among the involved IBD patients (n = 59), 28.81% had anxiety and 33.90% had depression. Linear discriminant analysis Effect Size (LEfSe) (LDA > 3.0) revealed that 4 genera ( Klebsiella, Alloprevotella, Barnesiella, Bacillus ) were enriched, while Sellimonas was depleted in the anxiety group. Enrichment of 2 genera ( Ruminococcus, Barnesiella ) were found in the depression group. In the anxiety group, valine, leucine and isoleucine degradation was enriched in fecal microbiota, with upregulation of 3-methyl-2-oxobutanoic acid involved in the above pathway. In the depression group, butanoate metabolism was enriched in fecal microbiota, with alpha-ketoglutaric acid involved. Lysine degradation were enriched in fecal microbiota, with pipecolic acid involved. Primary bile acid biosynthesis was depleted in fecal microbiota, with glycocholic acid involved. Pearson correlation analysis revealed a positive correlation between Alloprevotella and 3-methyl-2-oxobutanoic acid in the anxiety group. In patients with both anxiety and depression, four genera ( Subdoligranulum, Alloprevotella, Christensenellaceae R-7 group, Barnesiella ) were positively correlated with alpha-ketoglutaric acid. Conclusion In this study, the alteration of composition of fecal microbiota was identified, and differential genus associated with IBD patients with anxiety or depression or both were explored. Change in function of microbiota was also discovered by the detection of differential pathways and fecal metabolites, which were associated with IBD patients with anxiety or depression or both.